Cardiac paraganglioma: advantages of cardiovascular multimodality imaging (2018)
Primary cardiac tumors are very rare. The reported prevalence ranges from 0.001% to 0.03%. Cardiac paragangliomas are among the most infrequent tumors, making up <1% of all primary cardiac tumors. They are chromaffin cell tumors that produce and secrete catecholamines and are located in the adrenal medulla in 90% of cases and in the mediastinum in <2%.